Whoops I meant ..
Sqrt of x+3, not x+1..
(a+b)^2 = a^2 + ab + b^2
a+b)^2 = a^2 + 2ab + b^2
(sqrt of 4x+1)+(sqrt of x+3)=2
4x+1 + 2 (sqrt (x+3)sqrt(4x+1)) + x+3=4
5x+4 +2 (sqrt (5x+4)=4
square both sides
x=-12/5 or x=6/5
Hmmm. I get
4x+1 + 2√(4x^2+13x+3) + x+3 = 4
5x = -2√(4x^2+13x+3)
25x^2 = 4(4x^2+13x+3)
25x^2 = 16x^2 + 52x + 12
9x^2 - 52x - 12 = 0
(9x+2)(x-6) = 0
x = -2/9 , 6
But x=6 does not satisfy the original equation, so -2/9 is the only solution.
Answer this Question
Math Help please!! - Could someone show me how to solve these problems step by ...
math calculus please help! - l = lim as x approaches 0 of x/(the square root of...
Algebra - Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r ...
Math - How do you find a square root of a number that's not a perfect square? I'...
math,algebra,help - Directions are simplify by combining like terms. x radiacal ...
Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...
MATH - I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y ...
math - solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the ...
Inequality - When I solve the inquality 2x^2 - 6 < 0, I get x < + or - ...
math - determine the area of triangle abc when side ab= square root of x, side ...